Unlocking Women’s Empowerment towards Digital Inclusivity in East Kalimantan through Digital Competence Evaluation - Juwita, Rina; Rahayu, Diah; Nimatu Rohmah, Ainun; Dhemas Pawae, Resky (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
The ability to use different Internet-mediated forms is a basic competence in the digital era, which indicates that women, too, need to have adequate digital skills for daily activities. However, previous studies found that women have a lower digital literacy index than men due to their sociocultural role and expectations and less motivation to engage with technology among older individuals. Digital competence is essential to enhance digital inclusivity, especially for women in East Kalimantan Province, following the future challenges of the Capital City of Nusantara (IKN) development and Indonesia Digital Vision 2045. This study employed a quantitative approach, which entailed adapting seven dimensions of digital competence from the DigComp 2.0 model as research instruments: basic knowledge of hardware and software, information and data literacy, communication and collaboration, digital content creation, security, problem-solving, and career-related competencies. This study involved a sample size of 538 women. The findings offer theoretical insights into the employment of the DigComp 2.0 model within a specific context and recommendations for women’s empowerment strategies. The result showed that women’s digital competence level in East Kalimantan was high, except for the content creation and problem- solving. Another intriguing finding is that the level of education was not directly related to the level of digital competence, which contradicts previous studies. Future studies could employ the same instrument to corroborate the findings in this study across diverse sociocultural contexts in Indonesia. Another direction is to consider psychological variables that could influence digital competence.